Examining the influence of inflammatory bowel disease medications on sleep quality. Issue 3 (2nd February 2023) - Barnes, Alex; Spizzo, Paul; Bampton, Peter; Andrews, Jane M; Fraser, Robert J; Mukherjee, Sutapa; Mountifield, Réme
Abstract: Background and Aim: Inflammatory bowel disease (IBD) can disrupt sleep, leading to poor sleep quality. This may in part be due to the symptoms of IBD and the influence of pro‐inflammatory cytokines on sleep. This study aimed to investigate the potential influence of IBD medications on sleep quality. Methods: An online survey of adults with IBD was conducted, which included measures of sleep quality, IBD activity, anxiety, depression, and physical activity. Logistic regression was used to investigate possible associations between IBD medications (corticosteroids, immunomodulators, biologics, aminosalicyate) and outcome of poor sleep. A generalized linear model was built for outcome of sleep quality score. Results: There were 544 participants included in the final analysis, median age of 42, and 61% with Crohn's disease. Increased odds of poor sleep were seen in those taking opioids, medications for anxiety or depression, corticosteroids, vitamin D, methotrexate, and infliximab. A multivariate model was built incorporating demographic and IBD variables with opioids present in the final model and associated with increased odds of poor sleep. This was in addition to medications for sleep, depression, anxiety, IBD activity, and body weight. In a multivariate generalized linear model, opioids and methotrexate were associated with worse sleep quality scores. Conclusions: Opioids were associated with increased odds of poor sleep independent of other factors. This provides further support for avoiding these medications in people with IBD. Infliximab was associated with increased body weight and consequently increased odds of poor sleep. Abstract : In a large population of people with Inflammatory bowel disease, poor sleep was more common in those on opioids, infliximab, corticosteroids, vitamin D, and methotrexate. Opioids remained associated with poor sleep when adjusting for other influences of sleep quality including abdominal pain.